A novel oral medicated jelly for enhancement of etilefrine hydrochloride bioavailability: In vitro characterization and pharmacokinetic evaluation in healthy human volunteers - Ahmed Hassen Elshafeey; Rania Moataz El-Dahmy (Elsevier, 2022)
Etilefrine hydrochloride (ET) is a water-soluble drug that is used to treat hypotension, but it has a bitter taste and low bioavailability due to undergoing the first-pass effect. Thus, this study aimed to develop and evaluate oral medicated jelly (OMJ) containing ET that could offer an easily taken palatable dosage form with higher bioavailability. OMJ is a novel palatable drug delivery system that can easily be taken by pediatric and geriatric patients, as well as those with dysphagia. Moreover, OMJs offer rapid disintegration in saliva and rapid drug absorption through the buccal mucosa, avoiding the first-pass effect and increasing the drug bioavailability. Natural polymers such as pectin, guar gum, xanthan gum, tragacanth gum, and sodium alginate were used as jellifying agents, with the addition of calcium chloride as a crosslinking agent, to prepare OMJs using the heat and congealing method. The prepared OMJs were investigated by testing their viscosity, in vitro release, and texture analysis of firmness, consistency, stickiness, cohesiveness, springiness, gumminess, and chewiness using a texture analyzer. A full factorial design (21 × 51) was utilized to select the optimized OMJ. The optimized OMJ (J2), containing 4 % pectin, had a 7563 ± 55 cps viscosity, 8.32 ± 0.21 N firmness, 5.72 ± 0.18 µJ consistency, 1.30 ± 0.04 mJ stickiness, and 96.02 ± 3.74 % ET dissolved after 10 min. ET release was significantly increased (greater than4-fold) from the optimized OMJ compared with the market tablet. Moreover, the obtained results clarified the stability and the acceptable palatability of the optimized OMJ. The clinical investigation on healthy human volunteers revealed that the optimized OMJ (J2) had significantly higher Cmax (1.7 folds) when compared with the market tablet with a relative bioavailability of 154.55 %. Therefore, OMJs can be considered as promising, palatable, and easily swallowed dosage form that could enhance the bioavailability of drugs undergoing the first-pass effect.